2013
DOI: 10.2460/javma.243.7.1010
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based survey of the nature and perceived causes of injury to dogs participating in agility training and competition events

Abstract: These findings provided a basis for further experimental studies to identify specific mechanisms of various types of injury in dogs that participate in agility activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
91
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 27 publications
13
91
4
Order By: Relevance
“…Soft tissue injuries such as strains, sprains and contusions are common in agility; approximately 32% of dog athletes develop an injury [4, 5] and the biomechanical mechanism of injury is often unknown [5]. However, certain activities, such as jumping and climbing the A-frame obstacle, have a higher risk for injury [4, 5]. The shoulder has been identified in two recent retrospective surveys as the most frequently injured anatomical location [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft tissue injuries such as strains, sprains and contusions are common in agility; approximately 32% of dog athletes develop an injury [4, 5] and the biomechanical mechanism of injury is often unknown [5]. However, certain activities, such as jumping and climbing the A-frame obstacle, have a higher risk for injury [4, 5]. The shoulder has been identified in two recent retrospective surveys as the most frequently injured anatomical location [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…However, certain activities, such as jumping and climbing the A-frame obstacle, have a higher risk for injury [4, 5]. The shoulder has been identified in two recent retrospective surveys as the most frequently injured anatomical location [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several degenerative disorders have been identified in both humans and dogs involving the supraspinatus tendon including rotator cuff tears, calcifying tendinopathy (bony mineralisation within the tendon) and tendinosis (microtears within the tendon) (3,(5)(6)(7). ST is a term used to describe these clinical conditions and/or injuries in and around the tendon of the supraspinatus muscle, and is a cause of forelimb lameness, especially in human athletes and performance dogs (5,(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…2,5,20 A previous survey with agility dogs found that thirty-two percent of the population had some degree of orthopaedic lameness during training, and that fifty-three percent of those evaluated by a veterinarian were due to muscle or tendon injury. 5 The muscle is prone to acute strain from excessive stretch while engaged in eccentric contraction, wherein the external forces being driven across the muscle overload the contractile force of the muscle itself. 3,4,23,[28][29] The fibres of the muscle may then become disrupted and lose continuity, with additional disruption of the vascular supply leading to interstitial haemorrhage and swelling.…”
Section: Introductionmentioning
confidence: 99%